A Comprehensive Analysis and Splicing Characterization of Naturally Occurring Synonymous Variants in the ATP7B Gene - Zhou, Xiaoying; Zhou, Wei; Wang, Chunli; Wang, Lan; Jin, Yu; Jia, Zhanjun; Liu, Zhifeng; Zheng, Bixia (Frontiers in Genetics, 2021)
Next-generation sequencing is effective for the molecular diagnosis of genetic diseases. However, the identification of the clinical significance of synonymous variants remains a challenge. Our previous study showed that some synonymous variants in ATP7B gene produced splicing disruptions，leading to Wilson Disease (WD). To test the hypothesis that synonymous variants of ATP7B cause abnormal splicing by disrupting authentic splice sites or splicing regulatory elements, we used computational tools and minigene assays to characterize 253 naturally occurring ATP7B gene synonymous variants in this study. Human Splicing Finder (HSF) and ESE Finder 3.0 were used to predict the impact of these rare synonymous variations on pre-mRNA splicing. Then we cloned 14 different wildtype Minigene_ATP7B_ex constructs for in vitro minigene assay, including 16 exons of ATP7B gene. After computational prediction, 85 candidate variants were selected to introduced into the corresponding Minigene_ATP7B_ex constructs for splicing assays. Using this two-step procedure we demonstrated that 11 synonymous variants in ExAc database (c.1620C>T, c.3888C>T, c.1554C>T, c.1677C>T, c.1830G>A, c.1875T>A, c.2826C>A, c.4098G>A, c.2994C>T, c.3243G>A and c.3747G>A) disrupted RNA splicing in vitro, and two (c.1620C>T and c.3243G>A) of these caused a complete exon skipping. The results not only provided a reliable experimental basis for the genetic diagnosis of WD patients but also offered some new insights into the pathogenicity of synonymous variants in genetic diseases.